Analisis Efisiensi Keuangan Daerah dan Efektivitas Pendapatan Asli Daerah Terhadap Pertumbuhan Ekonomi di Provinsi Sulawesi Selatan - Muh. Fauzil Hidaya; Hasbiullah, Hasbiullah (ICOR: Journal of Regional Economics, 2024)
The economic growth in South Sulawesi has experienced fluctuations over the past 5 years, specifically 2018-2022, with unstable levels of regional financial efficiency and effectiveness of the Original Regional Revenue. Therefore, this study is directed to analyze the Regional Financial Efficiency Ratio and the Original Regional Revenue Effectiveness Ratio in South Sulawesi Province from 2008-2022, and to understand their impact on economic growth in the province. Using secondary data from the Directorate General of Fiscal Balance of the Ministry of Finance and the Central Statistics Agency of South Sulawesi Province, this study applies multiple linear regression analysis. The research results show that the Regional Financial Efficiency Ratio is in the less efficient criteria, while the Original Regional Revenue Effectiveness Ratio is in the effective criteria. In addition, this study found that the Regional Financial Efficiency has a negative and insignificant effect on economic growth, while the Effectiveness of Original Regional Revenue has a positive and significant effect on economic growth in South Sulawesi Province.